2020
DOI: 10.1017/s0950268820002757
|View full text |Cite
|
Sign up to set email alerts
|

Community movement and COVID-19: a global study using Google's Community Mobility Reports

Abstract: Google's 'Community Mobility Reports' (CMR) detail changes in activity and mobility occurring in response to COVID-19. They thus offer the unique opportunity to examine the relationship between mobility and disease incidence. The objective was to examine whether an association between COVID-19-confirmed case numbers and levels of mobility was apparent, and if so then to examine whether such data enhance disease modelling and prediction. CMR data for countries worldwide were cross-correlated with corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 52 publications
8
84
0
4
Order By: Relevance
“…Population mobility could reflect the impacts of NPIs, reopening policies, and public holidays, and estimate social movement during the current COVID-19 pandemic. It is closely related to COVID-19 outbreaks, which is in accordance with the findings of prior research [ 9 , 11 , 17 - 19 ]. This study adds value to previous studies by examining the impacts of population mobility on COVID-19 incidence at both the state and county level in South Carolina.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Population mobility could reflect the impacts of NPIs, reopening policies, and public holidays, and estimate social movement during the current COVID-19 pandemic. It is closely related to COVID-19 outbreaks, which is in accordance with the findings of prior research [ 9 , 11 , 17 - 19 ]. This study adds value to previous studies by examining the impacts of population mobility on COVID-19 incidence at both the state and county level in South Carolina.…”
Section: Discussionsupporting
confidence: 92%
“…Existing literature has suggested that population mobility may reflect the influences (both positive and negative) of NPIs, reopening actions, and public holidays [ 7 - 9 ]. For instance, in the early stages of the COVID-19 pandemic, the governor of South Carolina issued a series of NPIs, such as shelter-in-place and the closure of schools and nonessential businesses, to reduce social interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this finding is that we did not capture or account for the influences of contextual factors (i.e., population density) and the roles of mitigating factors (e.g., wearing face mask, practicing social distancing) [16,20,21]. Additionally, the Twitter-based mobility did not differentiate the social movement at different locations, such as movement around parks, workplace, and retail places, which show different impacts on COVID-19 incidence [6]. Furthermore, in this study, we only captured population mobility at state- and county- levels while population mobility at zip code level might provide more accurate prediction.…”
Section: Discussionmentioning
confidence: 99%
“…provides a comparable source of movement data from users of its applications: Google's "Community Movement Trends." 12 Another limitation is that data are obtained only from those users seeking directions, and presumably only from those mobile in unfamiliar locations, and is thus only an indirect indicator of general community mobility. It could be that there was increased reluctance to travel in unfamiliar locations during the COVID-19 pandemic, and levels of mobility in familiar well-known locations differed from those recorded by this dataset.…”
Section: Discussionmentioning
confidence: 99%